A mediação como mecanismo de pacificação urbana - Isoldi, Ana Luiza Godoy (2008)
This study aims to identify adequate resolution mechanisms for conflicts in the urban environment, especially those regarding urbanistic policies, for the purpose of concretizing the diffuse interests, collective or individual, public or private, in an ampler, more effective and efficient way, within the context of a Democratic Constitutional State, which requires public participation in city administration. The analysis iniciates with the new trends in Urbanistic Law and Legislation, which include a consensual public administration, describes several means to settle disputes either by agreement or by stipulation, with their respective mechanisms, that integrate the conflict resolution system, especially in what regards mediation and, finally, analizes social community mediation as a tool for urban pacification, as well as the possibilities of urbanistic mediation, mainly when it is applied simultaneously with the urbanistic instruments. The research method was reading of the bibliographic repertoire about the subject in the field of Legal Science, with contributions from other disciplines as well. The results led to the accomplishment of the intended objectives, especially by the identification of an adequate route for the resolution of urbanistic disputes, markedly in the context of judicial case administration